Al-Qur’an Dan Ilmu Kedigjayaan: Studi Living Qur’an Masyarakat Kalimantan - Bunyamin Bunyamin; Fuad Fansuri; Mukhtar Muhammad Salam; Akhmad Rijali Elmi; Sitti Sagirah (Universitas 17 Agustus 1945, 2023)
Al-Qur’an is a guide to life. Muslims generally practice receiving the Qur’an in various forms, reading, understanding, practicing, even in the form of socio-cultural reception. The study of the Living Qur'an in the Banjar community is also an effort by researchers to carry out a transformative ideology about the Al-Qur’an. The progress of Islamic civilization is greatly influenced by how people treat the Al-Qur’an in everyday life. In this research, it was found that the majority of Banjar people who live in the Kahlidiyah Rasyidiyah Islamic Boarding School believe that the Al-Qur'an contains various special prayers with certain virtues. People's reception of rajah also varies, including; Rajah is something that contains blessings and has certain powers because it is inscribed with verses from the Qur'an, so it can be concluded that the use of verses from the Qur'an in rajah is one of the many ways of glorifying the Qur'an.